Assessment of Pesticide Residues in Some Vegetables Grown in Kavrepalanchok and Bhaktapur Districts - Rawal, Deepa Shree; Rana, N; Shrestha, S; Sijapati, J (Nepal Journal of Science and Technology, 2013)
Pesticides have wide spread use and their toxic residues have been reported in various environmental matrices. Thus, the determination of pesticide residues in food commodities such as vegetables, cereals, fruits, and other environmental components like soil, water has become increasingly essential requirement for consumers, producers and authorities for food quality control. Therefore, monitoring of residue level and exposure assessment of organophosphate group of pesticides namely dichlorovos and methyl parathion was carried out in 30 winter and summer vegetables supplied in Kathmandu valley. It was found that the MRL value of dichlorovos exceeded in three types of vegetables whereas in case of methyl parathion the MRL value exceeded in two types of vegetables only. The estimated average daily intake (EADI) of dichlorovos exceeded the acceptable daily intake (ADI) in 18 vegetables, whereas, regarding methyl parathion the EADI exceeded the ADI in 10 types of vegetables. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 45-50 DOI: http://dx.doi.org/10.3126/njst.v13i2.7713